The Influence of Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) On Return On Assets (ROA) Study at PT. Bank Mandiri Syariah - Fauziyyah Sahar (SINTESA, 2022)
This study aimed to examine the effect of non-performing financing (NPF) and the Capital Adequacy Ratio (CAR) on Return On Assets (ROA). The data in this study are secondary data on the PT. Bank Syariah Mandiri period 2006-2013. The method of analysis used in this study is using multiple regression analysis. This shows that the influence of variables Non Performing Financing (NPF) and the Capital Adequacy Ratio (CAR) on Return On Assets (ROA) of 82.9%. Means a very strong independent variables affect the dependent variable. While partially Non Performing Financing (NPF) significant negative effect on Return on Assets (ROA) and the Capital Adequacy Ratio (CAR) is not significant negative effect on Return On Assets (ROA). Simultaneously Non Performing Financing (NPF) and the Capital Adequacy Ratio (CAR) had no significant effect on Return On Assets (ROA).